Effects of energy drink consumption on physical performance and perceptual responses among physically inactive university students - Sze, Chan Ming
Consumption of energy drinks (e.g. RedBull, Livita, Monster Energy) has been increasing during the past few decades, especially among University students. Researchers have reported improvements in exercise performance (i.e., endurance, agility) with the use of energy drink among athletes or physically active individuals, although these findings are equivocal. Currently, the effects of energy drink among physically inactive individuals is unclear. The aim of the present study was to examine the effects of energy drink on physical performance (i.e., agility performance, reaction times, short-term maximal performance) and perceptual responses (i.e., mood state, rating of perceived exertion (RPE), heart rate (HR), affect responses) in physically inactive university students. A randomized, repeated measures cross-over design was implemented in this study. A total of eleven physically inactive students (N = 11, 4 males and 7 females, age = 22.82 ± 0.98 years; height = 164.13 ± 4.81 cm; body-mass = 59.83 ± 13.88 kg; total MET-minutes/week = 578.73 ± 161.20) participated in this experimental study. All participants underwent two experimental conditions: energy drink (ED) condition and placebo condition (PD). Participants completed the Brunel Mood Scale (BRUMS) questionnaire before and after the exercise protocols. Subsequently, participants performed a 3-min warm-up by running on a treadmill at self-selected paced followed by agility t-test, simple visual tap reaction time test, and the 30-s Wingate test. A 3-min rest gap was given between each exercise trial. Perceptual responses, namely, RPE, HR and affect responses were measured and calculated immediately after these tests. Data were analysed using one-way repeated measures analyses of variance (ANOVA) to examine differences across dependent variables. Findings of the present study showed significant reductions in level of fatigue and the perception of depression scores in ED compared to PD in BRUMS. This study also indicates that affect response measured via feeling scale (FS) was significantly improved with the ingestion of ED in mean changes of score of FS during agility t-test (p = 0.001) while PD elicited a significant improvement (p = 0.02) in the mean changes of score of FS during 30s-Wingate test. Also, consumption of ED elicited a greater magnitude (p = 0.003) in the mean changes of score of felt arousal scale (FAS) during agility t-test compared to PD. In addition, this study revealed that ED leads to favourable changes of RPE (p = 0.039) than in PD among physically inactive individuals while performing tap reaction time test. Finally, there were no significant differences in other variables (i.e., agility t-test, tap reaction time test, and 30-s Wingate test) associated with the ergogenic effects of energy drink. Thus, in conclusion, this study demonstrated that ED ingestion has a positive effect on reducing the negative mood states which are fatigue and depression scores among physically inactive university students. In terms of affect responses (FS and FAS), ED consumption has showed several significant improvements than that of PD. Further studies and research are warranted for in depth understanding of the benefits of taurine-containing energy drinks on physical performance and perceptual responses among physically inactive individuals.